Machine Learning-Based Spatial Modeling of Land Surface Temperature in Butantã: Insights from SHAP Interpretability - Pereira, Williane G. S.; Melo, Gabriel V. de; Negreiros, Waldemiro J. A. G.; Costa, Fernando A. R.; Tamasauskas, Leonardo de O.; S. Junior, Claudomiro de S. de; Seruffo, Marcos C. R. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2026: Anais do XVII Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2026)
Accelerated urbanization has expanded urban heat islands, necessitating the precise monitoring of Land Surface Temperature (LST). This study spatially predicts LST in Butantã (SP) for 2018 and 2021 using a high-resolution multiscale approach. To capture the relationships between urban morphology and LST, XGBoost and LightGBM models were compared, with XGBoost demonstrating superior predictive performance (R 2 of 0.890 and 0.848). Applying the SHapley Additive exPlanations (SHAP) method to the winning model ensured explainability, revealing the dominance of impervious surfaces in warming, the strong mitigating potential of water bodies and vegetation, and the heat retention induced by topography in valleys.